2023
DOI: 10.1007/s11356-023-25904-x
|View full text |Cite
|
Sign up to set email alerts
|

Can environmental taxes and green-energy offer carbon-free E7 economies? An empirical analysis in the framework of COP-26

Abstract: The main cause of environmental degradation is carbon emissions, which puts environmental sustainability in jeopardy. This ecological worry, the obligation for which falls on all economic actors, has not gone undetected, and so in 2021, the Glasgow Climate Pact (COP: 26) was organized, with the primary aim of decreasing global carbon emissions. Because the Post-Glasgow Agreement goals represent a significant challenge to achieving ecological responsibility, pressure is applied to the participating nations. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 107 publications
1
5
0
Order By: Relevance
“…The relationship between green taxes and life expectancy also involves changes in people’s habits and ways of living ( 8 ). Individuals and businesses can be motivated to adjust their activities, particularly in the presence of a dynamic economic framework, such as through the use of green taxes ( 43 ). These behavioral changes could lead to healthier and more sustainable practices that promote greener lifestyles and enhance life expectancy.…”
Section: Background Of the Studymentioning
confidence: 99%
“…The relationship between green taxes and life expectancy also involves changes in people’s habits and ways of living ( 8 ). Individuals and businesses can be motivated to adjust their activities, particularly in the presence of a dynamic economic framework, such as through the use of green taxes ( 43 ). These behavioral changes could lead to healthier and more sustainable practices that promote greener lifestyles and enhance life expectancy.…”
Section: Background Of the Studymentioning
confidence: 99%
“…It has been noted that the potential advantages of green imports are lowering CO2 emissions. However, a number of di culties and obstacles have been noted, such as the barriers in the broad adoption of green imports will contain the high manufacturing costs of eco-friendly goods and their scarcity (Cao 2023;Hassan et al 2023a;Sarpong et al 2023). In addition, the green energy imports into international trade are hampered by regional variations in environmental rules and regulations.…”
Section: Green Imports and Co2 Emissionsmentioning
confidence: 99%
“…First, Studies have indicated that digital finance has the potential to expand the accessibility of eco-friendly financing options for renewable energy projects, especially in developing countries [ 28 ]. Digital finance facilitates transparent financing options, promotes innovative financial technologies’ advancement, and enhances funds’ availability for sustainable energy projects [ 29 , 30 ]. Digital financial technology enables transparent and secure transactions, while mobile payment solutions improve financial service accessibility in rural regions.…”
Section: Introductionmentioning
confidence: 99%
“…By implementing taxation on activities that harm the environment, governments can foster the adoption of cleaner practices and stimulate the advancement and utilization of renewable energy sources [ 31 ]. Tax credits and incentives are critical for promoting the broad use of renewable energy sources and attracting significant investments in environmentally beneficial projects [ 30 ]. Extensive research supports the premise that combining economic incentives with environmental goals might help steer greener energy sources more successfully.…”
Section: Introductionmentioning
confidence: 99%